Discovering the Cultural Identity of Manduro People in Sandur Performing Arts - Rahmi Febriani; Rifki Diaz Erlangga (Universitas Airlangga, 2022)
Sandur Manduro is one of the local traditions which led the understanding in discovering the cultural identity of Manduro people. This identity makes the culture more unique and particular which can be identified easily from others. This research had been done by a case study approach in order to observe, explore, and understand Sandur Manduro’s performing arts comprehensively and holistically. This study aimed to discover the local wisdom in Sandur Manduro which represents the cultural identity of the Manduro people. The data was obtained directly through the source of Sandur Manduro performing arts in Manduro Village, Kabuh, Jombang, East Java. The process of data collection has been carried out by unstructured and open-ended interviews through actors, ancestors, and audiences. As a result, amid the bewilderment of constructing the Oreng Manduro’s origin, Sandur has clearly projected how pluralism, the values of obedience, and portraits of agrarian society integrate with this performing art. These aspects actually have shown the cultural identity of the Manduro people.